'Voluntarily Childless': An Auto-ethnographic Account of a Man's Struggles in India. (June 2022) - Bahttacharyya, Anindya
This article is an account of the struggles of a man in a patriarchal cultural context, where the idea of childfree men is despised and regularly confronted. Autoethnography is a method and a means to story-telling not only of the struggles that a man faces but also is a living document of the interactions, relationships, acquaintances and family regarding a choice over voluntary parenthood. The idea of voluntary childless men is a rarity in Indian cultural context of compulsory motherhood, especially in a pronatalist culture. Women's struggles have been documented but it is rarely that a man's position is located.